2006
DOI: 10.1126/science.1120865
|View full text |Cite
|
Sign up to set email alerts
|

Dissociation of MgSiO 3 in the Cores of Gas Giants and Terrestrial Exoplanets

Abstract: CaIrO3-type MgSiO3 is the planet-forming silicate stable at pressures and temperatures beyond those of Earth's core-mantle boundary. First-principles quasiharmonic free-energy computations show that this mineral should dissociate into CsCl-type MgO cotunnite-type SiO2 at pressures and temperatures expected to occur in the cores of the gas giants + and in terrestrial exoplanets. At approximately 10 megabars and approximately 10,000 kelvin, cotunnite-type SiO2 should have thermally activated electron carriers an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

16
149
3
3

Year Published

2009
2009
2018
2018

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 179 publications
(171 citation statements)
references
References 21 publications
16
149
3
3
Order By: Relevance
“…For the silicate melting point, we assume the Lindemann melting law [58] 8) wherem andv are the mean atomic mass and volume, respectively, k B is the Boltzmann constant, h is the Planck constant divided by 2π , θ is the Debye temperature and f is the critical ratio of vibration amplitude to atomic spacing at melting. For applications to the core-mantle boundary of super-earths, we assume that the solid phase is MgSiO 3 post-perovskite [59,60], and compute the volume and Debye temperature as a function of pressure along the 1600 K adiabat from the thermodynamic model of [38]. We chose the value of f = 0.…”
Section: −2β Pmentioning
confidence: 99%
“…For the silicate melting point, we assume the Lindemann melting law [58] 8) wherem andv are the mean atomic mass and volume, respectively, k B is the Boltzmann constant, h is the Planck constant divided by 2π , θ is the Debye temperature and f is the critical ratio of vibration amplitude to atomic spacing at melting. For applications to the core-mantle boundary of super-earths, we assume that the solid phase is MgSiO 3 post-perovskite [59,60], and compute the volume and Debye temperature as a function of pressure along the 1600 K adiabat from the thermodynamic model of [38]. We chose the value of f = 0.…”
Section: −2β Pmentioning
confidence: 99%
“…According to Umemoto et al [2006a] a large decrease in enthalpy at the pyrite-type → cotunnite-type transition in SiO 2 stabilizes the breakdown products with respect to MgSiO 3 , due mainly to the higher density of the cotunnite-type SiO 2 + B2-MgO than MgSiO 3 -PPv. NaMgF 3 is a good analog material for MgSiO 3 because its breakdown occurs from the same thermodynamic driving force [Umemoto et al, 2006b].…”
Section: Introductionmentioning
confidence: 99%
“…[3] Recent first-principles calculations by Umemoto et al [2006a] proposed that the post-perovskite form of MgSiO 3 breaks down to an oxide mixture (MgO + SiO 2 ) at ∼1000 GPa, corresponding to the core-mantle boundary pressure in 10M È super-Earths. They predicted a strongly negative Clapeyron slope (dP/dT = −30 MPa/K) of the breakdown -at least an order of magnitude larger than the post-spinel transition.…”
Section: Introductionmentioning
confidence: 99%
“…For example the very existence of planetary cores, their masses, as well as the amount and distribution of heavy elements in the planets' core or in their envelopes, remain undetermined. Recently, Wilson & Militzer (2012) suggested that planetary cores, mostly composed of rock and ices, can be eroded and/or dissolve (depending on their mass) into the metallic H/He layers above, and thus be redistributed in the planetary envelope (see also Umemoto et al 2006). This can have significant implications for giant planets' thermal evolution, their radius contraction, and overall structure.…”
Section: Wasp-56b and Wasp-57bmentioning
confidence: 99%